Short-Term Electrical Load Forecasting of 150 kV Ternate System Using Optimally Pruned Extreme Learning Machine (OPELM) - Andi Muhammad Ilyas,; Fahrizal Djohar,; Muhammad Natsir Rahman,; Ansar Suyuti,; Sri Mawar Said,; Indar Chaerah Gunadin,; Satriani Said Akhmad,; Yulinda Sakinah Munim,; Mukhlis Muslimin,; Tanridio Silviati Abdurrahman,; Zulaeha Mabud,; Ramly Rasyid,; et al. (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Short-term electrical loads forecasting is one of the most important factors in the design and operation of electrical systems. The purpose of electric load forecasting is to balance electricity demand and electricity supply. The load characteristics of Ternate City vary, so this study uses the Optimally Pruned Extreme Learning Machine (OPELM) method to predict electrical loads. The advantages of OPELM are the fast-learning speed and the selection of the right model, even though the data has a non-linear pattern. The accuracy of the OPELM method can be determined using a comparison method, namely the ELM method. Mean Absolute Percentage Error (MAPE) is used as the accuracy criterion. The results of the comparison of accuracy criteria show that the predictive performance of OPELM is better than that of ELM. The minimum error average of the OPELM forecast test results shows a MAPE of 5,2557%, for Saturday's forecast, while the ELM method gives a MAPE of 6.4278% on the same day.